2022
DOI: 10.3390/ijerph191912710
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Selection and Common Injuries in Fitness Centers: A Systematic Integrative Review and Practical Recommendations

Abstract: Weight resistance training (RT) is an essential component of physical conditioning programs to improve the quality of life and physical fitness in different ages and populations. This integrative review aimed to analyze the scientific evidence on the relationship between exercise selection and the appearance of musculoskeletal injuries in physical fitness centers (PFC). The PubMed or Medline, EMBASE or Science Direct, Google Scholar and PEDro databases were selected to examine the available literature using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 124 publications
(128 reference statements)
1
8
0
Order By: Relevance
“…We aimed to perform a systematic integrative review on the effects of several adaptogens on depression-related outcomes besides evaluating the potential combination with physical exercise to optimize results. Similar to previous reports in peri- and postmenopausal women [ 89 ] and healthy individuals [ 90 ], it has been found that certain adaptogens might have low-to-moderate clinical effects to relieve anxiety and mild depression [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. It is important to note that the number of articles reporting the level of physical activity is very low and null for those combining an exercise program with adaptogen consumption.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We aimed to perform a systematic integrative review on the effects of several adaptogens on depression-related outcomes besides evaluating the potential combination with physical exercise to optimize results. Similar to previous reports in peri- and postmenopausal women [ 89 ] and healthy individuals [ 90 ], it has been found that certain adaptogens might have low-to-moderate clinical effects to relieve anxiety and mild depression [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. It is important to note that the number of articles reporting the level of physical activity is very low and null for those combining an exercise program with adaptogen consumption.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we used the optimized methodology established by Hopia et al [ 32 ] for the evaluation and analysis of scientific publications, including problem formulation, a literature search, evaluation, analysis, and presentation of findings. The systematic integrative approach has been used previously in health-related topics [ 33 , 34 , 35 ]. The results were reported according to the established guidelines of the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The aim was to synthesize the occurrence of literature regarding nutrition interventions for the injured athlete. Similar to previously published articles [ 36 ], the review methodology was enhanced by optimizing the stages of literature search, data evaluation, and data analysis in order to systematize the review process and improve the scientific soundness according to recommendations given by Hopia et al [ 37 ] and the PRISMA in Exercise, Rehabilitation, Sport Medicine and Sports Science (PERSiST) guidelines [ 38 ]. The protocol of this review was published and freely accessible at Figshare to avoid unnecessary duplication (DOI: 10.6084/m9.figshare.21399696).…”
Section: Methodsmentioning
confidence: 99%
“…Both leisure and competitive RT has been associated with injuries (Pirruccio and Kelly, 2019). RT injuries result from losing control while using weights and misusing equipment and can result in adaptive complications (Bonilla et al, 2022). However, the effect of continuous RT on the glenohumeral joint is unknown (Kolber et al, 2017).…”
Section: Introductionmentioning
confidence: 99%